Introduction to Chemicals from Biomass - Clark, James H. (Wiley Series in Renewable Resource, 2014)
the 1st edition: "Drawing on the expertise of the authors the book involves a degree of plant biology and chemical engineering, which illustrates the multidisciplinary nature of the topic beautifully" - Chemistry World